151k views
21 votes
Write the quadratic equation in factored form
x 2 + x - 12 = 0

User Shaun
by
4.3k points

2 Answers

11 votes
  • x²+x-12=0
  • x²+4x-3x-12=0
  • x(x+4)-3(x+4)=0
  • (x-3)(x+4)=0

Zeros are 3 and -4

User Ego Slayer
by
5.1k points
3 votes

Answer:

(x-3)(x+4)=0

Explanation:

We want to rewrite the following quadratic equation in factor form


{x}^(2) + x - 12 = 0

What's a quadratic equation?

Equations with second degree are called quadratic equations. The standard form of a quadratic equation is

  • ax²+bx+c=0

How to factor the quadratic equation?

The steps of factoring the quadratic are as follows:

  1. Figure out two terms whose sum is 1 and product is -12
  2. break up the middle term
  3. group if required
  4. factor the common terms

Factoring the quadratic:


{x}^(2) + x - 12 = 0 \\ \implies {x}^(2) + 4x - 3x - 12 = 0 \\ \implies x(x + 4) - 3(x + 4) = 0 \\ \implies \boxed{(x - 3)(x + 4) = 0}

Hence, the factored form of the quadratic equation is (x-3)(x+4)=0

User Stephen York
by
4.7k points